Swarna Jayanti Gram Swarozgar Yojna (SGSY)- Sustainable Approach for Livelihood of Rural Women - Singh, Ajay; Singh, Sanjay; Singh, Alka; Singh , KK; Singh, Dhananjai (Indian Journal of Extension Education, 2017)
The present investigation was carried out in Rewa district of Madhya Pradesh. The district has nine blocks. Out of which  four blocks were selected purposively. From these blocks five villages were selected purposively on the criteria of  maximum number of beneficiaries undertaking income generating activities. With a view to assessing the influence of  attributes of the rural women beneficiaries on their sustainable livelihood, chi-square test was applied to the data and  association of each attribute of the respondents was found out. It was observed that the attributes of the respondents viz,  education, size of land holding, farming experience, occupational status, annual income, longevity of membership had  significant association with their sustainable livelihood. The major constraint as perceived by the rural women  beneficiaries to sustain their livelihood lack of skill oriented trainings.
Keywords: Swarna jayanti gram swarozgar yojna (SGSY); livelihood; rural women